A three-dimensional flower-like NiCo-layered double hydroxide grown on nickel foam with an MXene coating for enhanced oxygen evolution reaction electrocatalysis. Issue 20 (30th March 2021) - Li, Xuemei; Zhang, Zilu; Xiang, Qiankun; Chen, Rongrong; Wu, Di; Li, Guangyao; Wang, Linjiang
Abstract : A three-dimensional flower-shaped layered double hydroxide is grown on MXene to fabricate a NiCo-LDH/MXene/NF hybrid electrocatalyst to enhance the OER performance. Abstract : Electrolysis of water is currently one of the cleanest and most efficient ways to produce high-purity hydrogen. The oxygen evolution reaction (OER) at the anode of electrolysis is the key factor affecting the reaction efficiency, which involves the transfer of four electrons and can slow down the overall reaction process. In this work, using nickel foam coated with MXene (Ti3 C2 T x ) as the carrier, a three-dimensional flower-shaped layered double hydroxide (NiCo-LDH) is grown on Ti3 C2 T x by a hydrothermal method to fabricate a NiCo-LDH/Ti3 C2 T x /NF hybrid electrocatalyst for enhanced OER performance. The results reveal that the hybrid electrocatalyst has excellent OER activity in alkaline solution, in which a low overpotential of 223 mV and a small Tafel slope of 47.2 mV dec −1 can be achieved at a current density of 100 mA cm −2 . The interface interaction and charge transfer between Ti3 C2 T x and NiCo-LDH can accelerate the electron transfer rate during the redox process and improve the catalytic activity of the overall reaction. This NiCo-LDH/Ti3 C2 T x /NF hybrid electrocatalyst may have important research significance and great application potential in catalytic electrolysis of water.